Evaluation of the antibacterial activity of a conventional orthodontic composite containing silver/hydroxyapatite nanoparticles - Ahmad Sodagar; Azam Akhavan; Ehsan Hashemi; Sepideh Arab; Maryam Pourhajibagher; Kosar Sodagar; Mohammad Javad Kharrazifard; Abbas Bahador (SpringerOpen, 2016)
Abstract Background One of the most important complications of fixed orthodontic treatment is the formation of white spots which are initial carious lesions. Addition of antimicrobial agents into orthodontic adhesives might be a wise solution for prevention of white spot formation. The aim of this study was to evaluate the antibacterial properties of a conventional orthodontic adhesive containing three different concentrations of silver/hydroxyapatite nanoparticles. Methods One hundred and sixty-two Transbond XT composite discs containing 0, 1, 5, and 10 % silver/hydroxyapatite nanoparticles were prepared and sterilized. Antibacterial properties of these composite groups against Streptococcus mutans, Lactobacillus acidophilus, and Streptococcus sanguinis were investigated using three different antimicrobial tests. Disk agar diffusion test was performed to assess the diffusion of antibacterial agent on brain heart infusion agar plate by measuring bacterial growth inhibition zones. Biofilm inhibition test showed the antibacterial capacity of composite discs against resistant bacterial biofilms. Antimicrobial activity of eluted components from composite discs was investigated by comparing the viable counts of bacteria after 3, 15, and 30 days. Results Composite discs containing 5 and 10 % silver/hydroxyapatite nanoparticles were capable of producing growth inhibition zones for all bacterial types. Results of biofilm inhibition test showed that all of the study groups reduced viable bacterial count in comparison to the control group. Antimicrobial activity of eluted components from composite discs was immensely diverse based on the bacterial type and the concentration of nanoparticles. Conclusions Transbond XT composite discs containing 5 and 10 % silver/hydroxyapatite nanoparticles produce bacterial growth inhibition zones and show antibacterial properties against biofilms.